A major new alliance in Australian healthcare: the Australian consensus framework for ethical collaboration in the healthcare sector. Issue 6 (14th June 2020) - Lipworth, Wendy; Fitzpatrick, Jane; Cosenza, Adrian; Kerridge, Ian; Subramanian, Peter; Verhoeven, Alison; Wells, Leanne
Abstract: The 'Australian Consensus Framework for Ethical Collaboration in the Healthcare Sector' (ACF) is an Australian initiative aimed at countering dysfunction and growing mistrust in the health sector through the development of a cross‐sectoral consensus framework. The development of this framework arose from Australia's involvement in the Asia Pacific Economic Cooperative (APEC) and has since become the largest of its kind internationally, with over 70 signatories representing professional bodies, industry organisations, hospital and health services associations, regulators and patient and advocacy groups. In this article, we describe and critique the framework and outline its implementation.